(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: The aims of this study were to establish parameters in panoramic radiography for interpretation of unilocular radiolucent lesions, and to compare the accuracy of diagnoses given by examiners before and after using these parameters. MATERIAL AND METHODS: In Part I, 12 specialists analyzed 24 images and the diagnostic criteria used by each examiner to make correct diagnoses were used to build a list of basic radiographic parameters for each pathology (ameloblastoma, keratocystic odontogenic tumor, dentigerous cyst, and idiopathic bone cavity). In Part II, this list was used by 6 undergraduate students (Un), 8 recently graduated dentists (D), 3 oral pathologists, 3 stomatologists, 3 oral radiologists, and 3 oral surgeons to diagnose the corresponding pathologies in the other set of 24 panoramic radiographs (T2). The same analysis occurred without using this list (T1). The method of generalized estimating equations (GEE) was used in order to estimate the probability of making a correct diagnosis depending on the specialty of the examiner, type of lesion, and moment of the evaluation, T1 or T2 (before or after they had access to the list of parameters, respectively). RESULTS: Higher values were obtained for the probability (GEE) of making a correct diagnosis on T2; the group Un presented the highest improvement (14.6 %); no differences between the probabilities were observed either between Un and D, or among the different groups of specialists. CONCLUSIONS: The use of panoramic radiographic parameters did allow improving the diagnostic accuracy for all groups of examiners.